Analyses for various doping structures of SOI-based optical phasemodulator using free carrier dispersion effectB - Mardiana, Bidin; Sahbudin, Saari; Menon, P.S; Haroon, Hazura; Hanim, Abdul Razak; Arsad, N.; Abdullah, H. (Elsevier GmbH, 2014)
tThis paper highlights the study on various structure of silicon-on-insulator (SOI) optical phase modula-tors based on free carrier dispersion effect. The proposed modulators employ the forward biased P-I-Ndiode structure integrated in the waveguide and will be working at 1.55 m optical telecommunicationswavelength. Three kinds of structure are compared systematically where the p+ and n+ doping positionsare varied. The modeling and characterization of the SOI phase modulators was carried out by 3D numer-ical simulation package. Our results show that the position of doping regions have a great influences tothe device performance. It was discovered that the best structure in this work demonstrated modulationefficiency of 0.015 V cm with a length of 155 m.